Rotational Changes in the Tibia After High Tibial Valgus Osteotomy: A Comparative Study of Lateral Closing Versus Medial Opening Wedge Osteotomy. Issue 14 (December 2020) - Kim, Joong Il; Kim, Bo Hyun; Han, Hyuk Soo; Lee, Myung Chul
Background: After high tibial valgus osteotomy (HTO), rotational changes in the tibia may occur, which can affect the biomechanics of the patellofemoral joint and may lead to anterior knee pain. Purpose: To compare the rotational changes in the tibia between closing wedge HTO (CWHTO) and opening wedge HTO (OWHTO). Study Design: Cohort study; Level of evidence, 3. Methods: Among the patients who underwent HTO between May 2012 and August 2015, 53 (28 CWHTO and 25 OWHTO) who had computed tomography scans before and at 1 year after the HTO were included. The following parameters were compared between CWHTO and OWHTO: (1) tibial torsion angle, (2) knee rotation angle, and (3) tibial tuberosity–trochlear groove (TT-TG) distance. During the last follow-up, patients were asked to rate their anterior knee pain when climbing the stairs, using the visual analog scale. Results: The tibial torsion angle significantly decreased (internal rotation of the distal fragment) after CWHTO (mean ± SD, –2.1°± 4.1°; P = .019) and OWHTO (–1.8°± 3.3°; P = .029). The knee rotation angle significantly decreased (external rotation of the proximal fragment) after OWHTO (–1.8°± 3.4°; P = .039) but was not changed after CWHTO (0.1°± 3.1°; P = .859). The mean TT-TG distance significantly decreased after CWHTO (–3.1 ± 3.0 mm; P < .001) but increased after OWHTO (2.0 ± 4.3 mm; P = .012). At the final follow-up (minimum, 4 years), the visual analog scale pain score during stair climbing was significantly higher after OWHTO than after CWHTO (3.1 ± 1.4 vs 2.2 ± 1.3, P = .024). Conclusion: Internal rotation of the distal fragment occurred after both CWHTO and OWHTO. However, external rotation of the proximal fragment and increased TT-TG distance occurred after OWHTO. Because such rotational changes could affect anterior knee pain, further studies are warranted to investigate the definite relationship between tibial rotational changes and anterior knee pain after HTO.